Influence of 3D Printing Parameters by FDM Method on the Mechanical Properties of Manufactured Parts - Zubrzycki, Jarosław; Estrada Barbosa, Quirino; Staniszewski, Michał; Marchewka, Magdalena (2022)
The manufacturing of machine parts with additive methods (AM) is of significant importance in modern industry. The development of 3D printers and all 3D printing technology is impressive. The ability to make parts quickly and relatively cheaply with AM gives excellent opportunities in terms of e.g., shortening the production preparation time. Proper selection of printing parameters allows for a significant reduction of printing time and production costs. Unfortunately, this has different consequences. Due to the course of the printing process and the parameters that can be set, the same product produced with different parameters has different mechanical properties – mainly different strength. This paper presents the impact of 3D printing parameters on the strength of manufactured parts. Strength tests were carried out on samples made in accordance with DIN EN ISO 527-1:2019. The samples were printed in technology FDM from three different materials, i.e. PLA (completely biodegradable), PETG (recycled material) and Smart ABS (material with minimal shrinkage). The tested samples were made in three levels of print filling – 10, 30 and 60% and with different types of filling – line, mesh and honeycomb. A series of static tensile tests were carried out to determine the strength of the samples produced with different printing parameters. Thanks to the obtained test results, it is possible to select the optimal printing parameters depending on the forecast load of the manufactured parts.